The Link between Oxidative Stress, Mitochondrial Dysfunction and Neuroinflammation in the Pathophysiology of Alzheimer's Disease: Therapeutic Implications and Future Perspectives - Maria Carolina Jurcău; Felicia Liana Andronie-Cioara; Anamaria Jurcău; Florin Marcu; Delia Mirela Ţiț; Nicoleta Pașcalău; Delia Carmen Nistor-Cseppentö (MDPI AG, 2022)
Alzheimer's disease (AD), the most common form of dementia, has increasing incidence, increasing mortality rates, and poses a huge burden on healthcare. None of the currently approved drugs for the treatment of AD influence disease progression. Many clinical trials aiming at inhibiting amyloid plaque formation, increasing amyloid beta clearance, or inhibiting neurofibrillary tangle pathology yielded inconclusive results or failed. Meanwhile, research has identified many interlinked vicious cascades implicating oxidative stress, mitochondrial dysfunction, and chronic neuroinflammation, and has pointed to novel therapeutic targets such as improving mitochondrial bioenergetics and quality control, diminishing oxidative stress, or modulating the neuroinflammatory pathways. Many novel molecules tested in vitro or in animal models have proven efficient, but their translation into clinic needs further research regarding appropriate doses, delivery routes, and possible side effects. Cell-based therapies and extracellular vesicle-mediated delivery of messenger RNAs and microRNAs seem also promising strategies allowing to target specific signaling pathways, but need further research regarding the most appropriate harvesting and culture methods as well as control of the possible tumorigenic side effects. The rapidly developing area of nanotechnology could improve drug delivery and also be used in early diagnosis.